Pupal Acoustic Behaviour of Troides helena helena (Linnaeus, 1758) (LEPIDOPTERA: PAPILIONIDAE) from West Java, Indonesia - Kurniati, Hellen; Peggie, Djunijanti; Sulistyadi, Eko (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTTroides helena helena (Linnaeus, 1758) can be found in Java and Bali. The larval and adult stages of this butterfly do not produce any sound, but the pupal stage produces sound in response to a touching stimulus. Sony PCM-M10 recorder and Pettersson M500 USB Ultrasound Microphone were used to record the sound. Adobe Audition 3.0 was used to visualize the oscillogram and audiospectrogram of the sound. Beyond our expectations, the pupae produce ultra sound hisses which are composed of many impulses. A one-day-old pupa has a frequency range between 0.2-40 kHz; however of 2-days to 18-days-old has a frequency range between 0.2-150 kHz. The sound wave consist of two sound elements, i.e. the audible sound element (0.2-20 kHz) and inaudible sound element (>20-150 kHz) and the bandwidth is between 200 Hz to around 150 kHz, with the strongest spectrum energy at around 2.6 kHz, 4 kHz, 6 kHz, 9 kHz and 23 kHz and some strong spectrum energy is also visible at around 40 kHz.Key words: acoustic, behaviour, butterfly, pupa, Troides helena helena